ANALISIS UKURAN PARTIKEL SILIKA HASIL EKSTRAKSI DARI BATU PADAS ASAL KABUPATEN KETAPANG KALIMANTAN BARAT - Risya Sasri; Nurlina Nurlina; Lia Destiarti; Intan Syahbanu (Tanjungpura University, 2018)
Analysis of particle size of silica was extracted from rocks from Ketapang Regency, West Kalimantan based on characterization using scanning electron microscope (SEM) have been carried out. The analysis was performed to determine the particle size change in extraction silica without and with activation using acid solution. SEM image processing was performed on a 10 μm scale at 350x magnification through the image-J software to determine the particle size distribution. The results of the analysis showed that the area and diameter of the silica particle extracted from rocks were 3,935 μm2 and 3,147 μm (without activation) and 4,28 μm2 and 3,267 μm (activated) respectively.